Constructing and modelling 3D GIS model in city engine for traditional Malay city - Abdullah, Ahmad Afiq Aiman; Hj. Mohd. Noor, Norzailawati; Abdullah, Alias (2017)
Malay urbanization is one of the oldest urbanization in the human history. Tradi-tional Malay also refers to the Malay races which full of custom, heritage, and also full with decency values while Traditional Malay City refers to the Malay City which establish before the British colonial era. Traditional Malay City have their own way of socio-economic aspect without adapting the Western influence. The formation of the Malay settlement and Malay Traditional Cities have their own uniqueness and specialty in terms of social life and integration between the land uses and building. Rapid development and uses of Geographic Information System (GIS) as a tool in urban planning nowadays has pushed the GIS technique further in visualization and presentation of urban planning data. Therefore, the main objective of this paper is to study on the formation and constructing the existing Traditional Malay city